Moderniser la ville, réaménager la rue à Ho Chi Minh Ville - Marie Gibert (EchoGéo, 2010)
This article considers the streets of Ho Chi Minh City as an original geographicalobject of researchthatallows to read the socio-spatial restructuration of the city in the currentcontext of urbanrenewal official policies. The urbanfabric network of Ho Chi Minh City is first and foremost a double foreigninheritagefromboth the Chinese and the French periods. It thendevelopped by itselfduringthreedecades. This urbanhistoryled to the development of a very dense network of narrowalleys, withmultiformurbanfunctions. The current official redefinition of the streetsscaleaims to allow for the verticalisation of the buildings environment. Then, theseprojects of streetrenewalenables us to examine the variousmodalities of streetrenewal and its new appropriation by the urbancitizens.